Optimal default policies in defined contribution pension plans when employees are biased - Asen Ivanov (Queen Mary University of London, School of Economics and Finance, 2018)
This paper analyses a model in which employees are biased in their perception of their optimal contribution rates or asset allocations in defined contribution pension plans. The optimal default is characterised as a function of the parameters. It is shown that, for some values of the parameters, forcing employees to actively decide is the optimal default policy. The total loss in the population at the optimal default policy can be nonmonotone in the parameters in counterintuitive ways.
Keywords: D14; D91; J26; J32; 330; optimal defaults; libertarian paternalism; nudging; pension plan design